Transformasi Berpikir Kritis Siswa Melalui Pendekatan Inkuiri Dalam Menulis Esai Argumentatif - Wakhibah Dwi Khusnah; M. Subhan (Journal of Innovative and Creativity, 2026)
Critical thinking skills are essential competencies in the digital era, particularly in constructing evidence-based arguments. This study aims to analyze the transformation of students’ critical thinking skills through the implementation of an inquiry-based approach in argumentative essay writing. This qualitative research, employing a case study design, was conducted at MA Al Fatah. Data were collected through classroom observations, in-depth interviews with teachers and 12th-grade science students, and document analysis of students’ essay drafts. Data analysis techniques included data reduction, data display, and conclusion drawing, with technical triangulation to ensure the validity of findings. The results indicate that the inquiry approach significantly shifts the students’ role from passive information recipients to independent researchers. The exploration phase, utilizing driving questions, successfully reduced writer’s block, while the investigation phase enhanced students’ information literacy in verifying authentic data sources. The pinnacle of cognitive transformation was observed in the students' ability to construct coherent logical flows and present counter-arguments objectively. The average student evaluation scores, ranging from 87 to 90, confirm the effectiveness of this method. This study concludes that the inquiry method not only improves writing quality but also strengthens students’ independent thinking and metacognitive awareness, which are crucial for higher education.